Analysis of primary productivity and trophic status of Kuala Gigieng waters Aceh Besar for sustainable fisheries management. Issue 1 (November 2021) - Nurfadillah, N; Dewiyanti, I; Yunus, M; Mellisa, S; Octavina, C
Abstract: Kuala Gigieng is one of the estuary areas in Aceh Besar Regency. This research is about the analysis of chlorophyll-a and trophic status of Kuala Gigieng waters in the context of sustainable fisheries management. This research was conducted in April 2019 in the water of Kuala Gigieng. This study aims to determine the trophic status of the waters, the value of chlorophyll-a and the abundance of phytoplankton in the Kuala Gigieng waters. Determination of observation stations using random stratified sampling method. Analysis of chlorophyll-a using the Trichomatic method. Analysis of the trophic status of the waters with the Trix method. The results showed that the waters of Kuala Gigieng were categorized as high fertility (eutrophic). The value of chlorophyll-a ranged from 0.21 u.g/l - 5.56 ug/l, and the value of net primary productivity (NPP) ranged from 3.47-27.77 mgC/m 3 /hour and the value of gross primary productivity (GPP) ranged from 5.20-32.98 mgC/m 3 /hour. Meanwhile, the abundance of plankton ranged from 133.33-207.40 ind/l. Water quality parameters are still suitable for the growth of plankton in Kuala Gigieng waters.